Sistem pakar pencarian maklumat berasakan queri (EsQIR) / Suzana Yusof - Suzana , Yusof (2003)
The title of my project is Expert System Query-based information Retrieval (EsQiR) From database which focused on job recruiting in IT. It is like the diagnosis system which diagnose the personality, aptitude, skills, interests of an individual that suits the job in IT. It is based on the question-answering form the simulate the answer and give the output to the user. The main objective is to assist the job recruiter or Join interviewer in finding the best candidate for the job in IT. The job recruiter that deal with the IT Company will find the best candidate for the company. The scope for the project is the qualified students with degree/diploma in Computer Science or Information Technology, job recruiter or job interviewer in IT and any user that willing to try the system. The system will recognize the characteristic that suits the job. The system focused on five specific position. They are programmer, system analyst, web designer, graphic designer and database administratoe. It is discover from the manual system that we use to find the job ourselves whether from friends, mass media, and so on. IT used the waterfall model and development process in Expert System. The system use the software Visual prolog 5.1 as a major software and embedded with image from Adobe Photoshop 6.0. The hardware that placer in the items also being used. Functional requirement and non-functional requirement also being explained in the project. Rule-based system is going to used as knowledge representation technique and forward chain as an inference technique. Interface module also presented to give a view to the user.